30 Rapid trio whole exome sequencing (R14) of an undiagnosed child, in the context of a new pregnancy. (15th December 2021) - Koutsogianni, Maria; Wakeling, Emma; Male, Alison; Stals, Karen; Ashraf, Tazeen
Abstract : The NHS R14 rapid Trio Whole Exome Sequencing (WES) service was introduced in 2019 and aims to provide a diagnosis for children with severe disorders for whom a diagnosis is needed to aid clinical management, or in the context of a new pregnancy, where a couple has a previous child with a likely genetic disorder that remains undiagnosed. The proband in this circumstance could be a deceased fetus, or a deceased or living child. An agnostic approach is utilised to identify novel variants in the proband when compared with parental DNA (trio analysis). All cases are analysed at the Exeter Genomics Laboratory. The aim of this audit was to retrospectively analyse cases that underwent rapid R14 trio WES in an existing pregnancy. We have looked at all cases that came through the North East Thames Clinical Genetics service from October 2019 onwards. We demonstrate our findings on whether: There were implications to the management of the existing pregnancy (prenatal testing and/or termination of pregnancy). There were changes to future reproductive options (e.g., Early prenatal testing or Referral for Pre-Implantation Genetic Testing- PGT). There were implications for family members (cascade testing and/or screening). We collected data from 28 cases. Women were tested between 6 to 36 weeks of pregnancy. In 57% a new diagnosis was made in the undiagnosed proband. From those, 43% of the pregnancies had prenatal testing. Overall, in 87% pregnancy continued (no variant was identified, there was a low recurrence risk, or a Variant of Unknown clinical Significance was identified). In 10% the result led to termination of the affected pregnancy. In 2 cases, the families tested were referred for PGT and more family members were tested. No diagnosis was made in 25% cases with a clinical phenotype in previous children.